Examining linkages between Smart Villages and Smart Cities: Learning from rural youth accessing the internet in India. (November 2018) - Fennell, Shailaja; Kaur, Prabhjot; Jhunjhunwala, Ashok; Narayanan, Deapika; Loyola, Charles; Bedi, Jaskiran; Singh, Yaadveer
Abstract: The literature on Smart Cities has not as yet paid adequate attention to the rural sector, and the potential in villages for creating smart and sustainable solutions for the 21st century. This paper focuses on linking proposed smart city strategies to smart village policies to ensure that rural youth have improved opportunities for employment through ICT initiatives to ensure digital inclusion, using primary surveys undertaken in India. The motivation was to understand how mobile telephony could be a catalyst to create Smart Villages in India, where young people can chart out new pathways to realize their aspirations with regard to tertiary education and new avenues for diversifying into rural non-agricultural employment. We use data obtained from a household survey in villages in the states of Punjab and Tamil Nadu to examine the mobile phone usage preferences of rural educated youth to identify the way forward in improving the accessibility of services on the supply side. We make the case that where youth are using mobile phone access to increase their social information base it is indeed possible that the new social media groups formed by rural youth become a powerful conduit for generating new employment opportunities. The key to accessing this solution is to use a demand driven model for mobile services that would permit a bottom of governance model to generate sustainable growth of enterprises and improved human development of these villages. Highlights: The need for linking Smart Cities and Smart Villages is identified. The current situation on Smart Cities thinking in India is described. The opportunity for using ICT to understand rural youth aspirations is set out. The nature of youth preferences for telecommunication services in rural Punjab and Tamil Nadu are analysed. The benefits of using bottom up generated data to improve matching of supply and demand is established.